If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = 6(x + -2) Reorder the terms: -10 + 6x = 6(x + -2) Reorder the terms: -10 + 6x = 6(-2 + x) -10 + 6x = (-2 * 6 + x * 6) -10 + 6x = (-12 + 6x) Add '-6x' to each side of the equation. -10 + 6x + -6x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 + 0 = -12 + 6x + -6x -10 = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 = -12 + 0 -10 = -12 Solving -10 = -12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2(8p+2)-3(2-7p)-2(4+2p)=0 | | 4v-10-4v=5 | | 6(4-5X)=234 | | (2x+13)(2x+13)=8 | | (9x+1)(9x-1)= | | 5(-6X-7)=145 | | 16t^2+84t= | | 5(1+4y)=2(3+10y) | | 2(2-x)-(4-x)=-5 | | 2.5a-6=1.12a-1.86 | | x^2-15+x^2-36= | | 9(x+12)-4x=143 | | -3(w+5)+7=-23 | | 3x+1-5(x+1)=6x+3 | | -7(-6X-2)=-448 | | X(2x+1)=105 | | -2y=14 | | 7(2x-3)=3+5(3x-5) | | 75=3(-6m-5) | | 7(3+2X)=-49 | | 16t^2+122t= | | 0=-16t^2+15t+100 | | v^2-7v+6= | | 12x^2-13xy-14y^2=0 | | -3(4z+4)=4(3z-3) | | 3(m-4)+3=21 | | 24r+24(r+3)=408 | | 3(2-x)-5=4(x+2) | | -x^2(13x+9)-8x^2-25x^3= | | 6(8+4X)=240 | | i^2=x | | x-3=2x+18 |